PROSES KREATIF: STUDI PADA KAMPANYE IKLAN TOKOPEDIA SELALU ADA SELALU BISA - Sekar Kusuma Rani (2022)
In this modern era, marketing activities are growing rapidly. Various companies compete to develop their products to be the best among their competitors. Advertising is one form of marketing communication that is most often used by companies to disseminate information about the products or services they use. TVC or Television Advertising, a brand created by an advertising agency, has a long process and involves many people until it can finally be broadcast in a media. Advertising agencies are required to have a better strategy when compared to the advertisements of their clients' competitors. One of the most important and can be said is in terms of message packaging. The process of packaging messages is carried out by the creative division, this division is expected to produce new things or ideas that are different and unique but still have to remember the main goal, namely "selling". Then the idea is packaged into a creative product in the form of an advertisement. Tokopedia advertisements through the Selalu Ada Selalu Bisa Campaign in collaboration with BTS have interesting things to know about the creative process. Through this research, which uses the Case Study method, it explains the creative process that occurs when looking for ideas to the process of working on the BTS version of the Tokopedia Selalu Ada Selalu Bisa Advertisement.The final result of this research shows that the Tokopedia Campaign is Selalu Ada Selalu Bisa be a product-oriented campaign that goes through only four stages of the creative process, namely; Immersion, Ideation, Brainfog and Evaluation. And also that the Domain elements contained in this campaign are not; Learning from previous Tokopedia advertisements, K-Pop Culture, especially BTS fans, and Indonesian Culture itself. The Fields' participation is also one of the important indicators in the results of this study because it was found that BTS Management is one of the compositions in these elements. And the elements of The Creators also not only mention one but also credit one creative team from the Flock Creative Network.